2015
DOI: 10.1182/blood-2015-03-633594
|View full text |Cite
|
Sign up to set email alerts
|

α-Globin as a molecular target in the treatment of β-thalassemia

Abstract: The thalassemias, together with sickle cell anemia and its variants, are the world’s most common form of inherited anemia, and in economically undeveloped countries, they still account for tens of thousands of premature deaths every year. In developed countries, treatment of thalassemia is also still far from ideal, requiring lifelong transfusion or allogeneic bone marrow transplantation. Clinical and molecular genetic studies over the course of the last 50 years have demonstrated how coinheritance of modifier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 93 publications
5
120
0
1
Order By: Relevance
“…We published these findings in a recent review article in 'Blood' where we concluded that a reduction of α-globin levels by 25%-50% in patients with β-thalassaemia should reduce or in fact eliminate the need of blood transfusion and could lead to a possible 'cure' 14 . However, to use this phenomenon as a therapeutic tool, we need to selectively reduce the production of α-globin without affecting the production of β-globin.…”
Section: Natural Reduction Of α-Globin In Patients With β-Thalassaemiamentioning
confidence: 99%
“…We published these findings in a recent review article in 'Blood' where we concluded that a reduction of α-globin levels by 25%-50% in patients with β-thalassaemia should reduce or in fact eliminate the need of blood transfusion and could lead to a possible 'cure' 14 . However, to use this phenomenon as a therapeutic tool, we need to selectively reduce the production of α-globin without affecting the production of β-globin.…”
Section: Natural Reduction Of α-Globin In Patients With β-Thalassaemiamentioning
confidence: 99%
“…3 Several genetic modulators [4][5][6][7][8] and cis-regulatory elements [8][9][10][11][12] involved in the regulation of human fetal hemoglobin (HbF), and concomitant a-thalassemia (MIM 604131) have been identified as ameliorators of b-thalassemia. 13 These modifiers included HBG2: À158C>T (NC_ 000011.9: g.5276169G>A, rs7482144, or XmnI polymorphism) in the b-globin cluster identified to be linked to HBG1: þ25G>A polymorphism (NC_000011.9: g.5271063C>T or rs368698783), 12,14 and the master genes involved in the regulation of fetal-to-adult hemoglobin (Hb) switching, including B cell CLL/lymphoma 11A (BCL11A [MIM 606557]), 5,8,15 Kruppel-like factor 1 (KLF1 [MIM 600599]), 6,15 and MYB (MIM 189990). 7,15 Identifying regulators of Hb switching including these genetic variants could provide promising predictors of b-thalassemia severity and therapeutic targets for re-activating HbF production.…”
Section: ]-Hbg2 [Mim 142250]-hbg1 [Mim 142200]-hbd [Mim 142000]mentioning
confidence: 99%
“…With the unraveling of complex genetic and environmental factors modulating clinical severity, new potential therapeutic approaches are under development [e.g., (65,147)]: gene switching (19) that includes HbF induction by hydroxyurea; stem cell transplants; gene therapy; pharmacological targeting of defective erythropoiesis; targeting free a-chains and with a-Hb chaperones; and countering the vasculature depletion of NO from chronic hemolysis (18,19,36,102,111,133,179,189).…”
Section: Current Therapeutics Addressing Oxidative Stress and Iron Ovmentioning
confidence: 99%